2012
DOI: 10.1136/medethics-2012-101056
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent and routinisation

Abstract: This article introduces the notion of 'routinisation' into discussions of informed consent. It is argued that the routinisation of informed consent poses a threat to the protection of the personal autonomy of a patient through the negotiation of informed consent. On the basis of a large survey, we provide evidence of the routinisation of informed consent in various types of interaction on the internet; among these, the routinisation of consent to the exchange of health related information. We also provide evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 17 publications
1
37
0
1
Order By: Relevance
“…a habitual, unreflective act. 22 In a recent study on consent behaviour in relation to the use of webportal containing personal health data, we have provided evidence of routinization. 23 The users of the portal are required to consent to the terms and conditions of use and the data protection policy of the site before use on the basis of being informed about these.…”
Section: Maximally Informed and Deliberated Preferencesmentioning
confidence: 99%
“…a habitual, unreflective act. 22 In a recent study on consent behaviour in relation to the use of webportal containing personal health data, we have provided evidence of routinization. 23 The users of the portal are required to consent to the terms and conditions of use and the data protection policy of the site before use on the basis of being informed about these.…”
Section: Maximally Informed and Deliberated Preferencesmentioning
confidence: 99%
“…Thus, we have previously shown that users with a short, medium or long university education tend to read more of consent materials [2]. This difference may be explained by the difference in the kind of activity requiring consent and the provider of the service.…”
Section: Discussionmentioning
confidence: 92%
“…Our previous studies of routinisation in relation to the use of various forms of ICT-services have revealed (1) that routinisation-indicated by the failure to read as well as reasons for not reading-occurs to significant degree across these services [2,22], and (2) that there is some evidence to the effect that the extent of routinisation is correlated with gender, education, age, and use of the internet such that the greater the level of routinisation the greater the ratio of (1) male users, (2) less educated, (3) younger and (4) extensive internet-users [3].…”
Section: Previous Results and Current Studymentioning
confidence: 99%
See 2 more Smart Citations